A self-regulated learning approach to extensive listening and its impact on listening achievement and metacognitive awareness - Zeng, Yajun; Goh, Christine C. M. (Studies in Second Language Learning and Teaching, 2018)
The role of self-regulation in general learning has been investigated for some time now. Its significance and contribution to second language (L2) listening, however, has yet to be discussed extensively with empirical support. This article reports a case study involving four college EFL students in China over a six-month period of self-regulated learning (SRL) in developing their listening in independent settings. The study examined how the achievement and metacognitive awareness of four high-achieving and low-achieving listeners may have been affected by strategies they used for self-regulating extensive listening activities. It also examined the learners’ engagement during four phases of self-regulated listening, namely, task definition, goal setting and planning, strategy enactment, and metacognitive adaptation. Findings revealed substantial differences in the two groups’ metacognitive engagement in three SRL phases. The article argues that the achievements of the respective learners in listening development were affected by these differences. Pedagogical implications of a self-regulated learning approach in extensive listening for L2 listening development are discussed.